Performance and carcass characteristics of Chianina-X steers - Jack G. Riley; G. Fink (Kansas Agricultural Experiment Station Research Reports, 1975)
Chianina-X steers gained consistently during a 151-day finishing test and produced high yielding carcasses with 0.06 in. fat and 1.71 square of loin per hundred pounds of carcass. Average USDA quality grade was between high good and low choice.
Keywords: Cattlemen& #x27; s Day; 1975; Report of progress (Kansas State University. Agricultural Experiment Station); 230; Beef; Performance; Carcass characteristics; Quality grade